Recommendations and Practical Guidance for performing and reporting validation studies according to the Universal Standard for the validation of blood pressure measuring devices by the Association for the Advancement of Medical Instrumentation/European Society of Hypertension/International Organization for Standardization (AAMI/ESH/ISO) - Stergiou, G; Palatini, P; Asmar, R; Ioannidis, J; Kollias, A; Lacy, P; McManus, R; Myers, M; Parati, G; Shennan, A; Wang, J; O’Brien, E (Lippincott, Williams and Wilkins, 2019)
In the past 30 years, several organizations have developed protocols for clinical validation of blood pressure measuring devices. An international initiative was recently launched by the US Association for the Advancement of Medical Instrumentation (AAMI), the European Society of Hypertension Working Group on Blood Pressure Monitoring (ESH) and the International Organization for Standardization (ISO), aiming to reach consensus on a universal AAMI/ESH/ISO validation standard. The purpose of this statement by the ESH Working Group on Blood Pressure Monitoring is to provide practical guidance for investigators performing validation studies according to the AAMI/ESH/ISO Universal Standard (ISO 81060–2:2018), to ensure that its stipulations are meticulously implemented and data are fully reported. Thus, this statement provides: a list of key recommendations for validation studies of intermittent non-invasive automated blood pressure measuring devices according to the AAMI/ESH/ISO Universal Standard; practical stepwise guidance for researchers performing these validation studies; a checklist for authors and reviewers of such studies; an example of a complete validation study report.